Effect of long-term grazing on the contents of phenolic compounds in Carex and Aster plants in Mongolia - Purevdorj Erdenetsogt; Nomin Munkhbat; Enkhriimaa Narmandakh; Tuvshintogtokh Idree; Chuan-Ming Yeh; Munkhtsetseg Tsednee (Mongolian Journal of Chemistry)
Long-term grazing changes the plant diversity and their growth significantly. At the metabolite level, the contents and compositions of the specialized metabolic compounds in plants could also be altered under long-term grazing conditions. To understand the metabolic changes caused by the grazing stress, in this study, we compared the contents and compositions of major phenolic compounds, together with total flavonoid contents, in two grazing-tolerant plants, Carex duriuscula and Aster hispidus, and two grazing-non-tolerant plants, Carex pediformus and Aster alphinus, and a local native plant Stipa baicalensus under long-term grazing conditions in Mongolia. Our results showed that long-term grazing has altered the contents and compositions of phenolic compounds and flavonoids both in above-ground tissues and roots of the analyzed five plants. Interestingly, such effects could appear to differ depending on plant species. These results provide the first comparative study of metabolite changes in grazing-tolerant and grazing-non-tolerant plants under overgrazing stress in the country.